âGANGâ KAMPUNG KOTA SEBAGAI RUANG PUBLIK MULTI FUNGSI - Ramelan, Rubianto; Handayani, Sri (-)
"Gang" is walking area applied as supporting facilities for circulation for in and out setlement of urban settlement which is the existing has become part of environmental variation urban which is inveterate there is in big towns in Indonesia.. Public residence culture in town kampong coloured by traditional life values in life is having neighbour and going into society influences their position in looking and utilizes road(street space. Gang which ought to be supporting facilities for circulation property of public is treated likely part of area of its. The thing mirror from usage pattern of road(street space in their everyday life. Road(street space which is public domain utilized as medium to do various public spirited not only activities but also having the character of personal. Road(street space in settlement of town kampung public becomes multifunction.Road (street space which ought to become public area often disturbed by behavior of dweller activity in right left along the length of gangway line. Gangway likely becomes area of property of dweller and its(the public is often is disturbed, intervenced even is dregs.